State Platform Capitalism: The Geopolitical Dynamics of Sustainable Digital Power in the US and China - Ullah, Naqeeb; Imran, Muhammad; Shafqat, Rafia; Sultan, Burree (2024)
In the contemporary digital landscape, digital power has emerged as a critical factor influencing global economic and geopolitical dynamics. This study examines the interplay between government regulations and technological innovation in shaping sustainable digital power, focusing on the United States and China. Leveraging the theory of state capitalism, the research integrates these variables into a comprehensive framework to explore their combined impact. Through a detailed literature review, the study highlights the importance of effective regulatory frameworks and continuous technological advancements for enhancing sustainable digital power. Using a robust methodological approach, the findings reveal significant positive relationships between government regulations, technological innovation, and sustainable digital power. The study underscores the necessity of a balanced approach to regulation and innovation to maintain a competitive edge and secure national interests. The contributions of this research are vital for policymakers and industry stakeholders, providing insights into how regulatory policies and technological investments can be optimized to enhance sustainable digital capabilities. This study fills a critical gap in the literature by offering a holistic understanding of digital power dynamics and its implications for global and national strategies. The paper concludes with practical recommendations and directions for future research.